The s - d exchange model as the underlying mechanism of magnetoresistance in ZnO doped with alkali metals - Zapata, María Cecilia (2019)
High field magnetoresistance has been studied in epitaxial n-type ZnO:Na and ZnO:Li thin films in a temperature range between 4 K and 150 K. The resulting negative magnetoresistance can be well fitted using a semiempirical model of Khosla and Fischer based on third order contributions to the s-d exchange Hamiltonian. The parameters obtained from this model were carefully analyzed. One of these parameters is related to a ratio between electron mobilities at zero field (a non-exchange scattering mobility and an exchange or spin dependent one ). From Hall effect measurements was obtained, displaying a weak temperature dependence in accordance with highly n-doped ZnO while the extracted exhibits an anomalous T-dependence. On the other hand, our magnetoresistance data cannot be properly fitted using Kawabata´s expression based on a weak-localization model.